2016
DOI: 10.1007/s11356-016-7331-8
|View full text |Cite
|
Sign up to set email alerts
|

Residue decline and risk assessment of fluopyram + tebuconazole (400SC) in/on onion (Allium cepa)

Abstract: A method was validated for estimating fluopyram and tebuconazole in onion on LC-MS/MS using dispersive QuEChERS. Three sprays of a combination fungicide fluopyram + tebuconazole (Luna experience, 400 SC) were applied @ 75 + 75 and 150 + 150 g a.i. ha at an interval of 10 days on onion using Knapsack sprayer. First spray was made at bulb setting stage. Spring onion samples were drawn at 0 (1 h), 1, 3, 5, 7, 10, 15, and 20 days and matured onion bulb at harvest (52 days) after the last spray. Soil samples were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…The impact of pesticide on human health, is not an easy and precise process because of differences in the periods and the levels of exposure, type of pesticide (with respect to toxicity), the geographic and meteorological characteristics of the agricultural areas where pesticides are applied etc [21,22]. Considering the human health risk due to pesticide toxicity and exposure, a greater risk is expected when the use of pesticides on food crops exceed maximum residue limit (MRL) which may leads to unwanted residues and constitute barriers to exporters and domestic consumptions.…”
Section: Risk Assessment Of Ethion In Cucumber Fruitmentioning
confidence: 99%
“…The impact of pesticide on human health, is not an easy and precise process because of differences in the periods and the levels of exposure, type of pesticide (with respect to toxicity), the geographic and meteorological characteristics of the agricultural areas where pesticides are applied etc [21,22]. Considering the human health risk due to pesticide toxicity and exposure, a greater risk is expected when the use of pesticides on food crops exceed maximum residue limit (MRL) which may leads to unwanted residues and constitute barriers to exporters and domestic consumptions.…”
Section: Risk Assessment Of Ethion In Cucumber Fruitmentioning
confidence: 99%
“…Up to date, fluopyram dissipation studies can be divided into those carried out in open fields and ingreenhouses. Open fields studies focus predominantly on the behaviour of the parent compound without taking into account the degradation compounds, 11,[16][17][18] although in one of them a single degradation compound was identified. 9 Also there is only one study conducted in greenhouse in which its degradation compounds were studied, 19 but the crop was in soil.…”
Section: Introductionmentioning
confidence: 99%
“…According to Patel et al, 6 half life of fluopyram was 8.85 and 9.12days, respectively in recommended and double dose. Dong & Hu 15 showed half life of 6.48days for fluopyram in watermelon.…”
Section: Dissipation Of Insecticidesmentioning
confidence: 98%
“…In chilli, Saha (2016) 5 found a half life of 1.161 and 1.241days for single (100g a.i./ha) and double (200g a.i./ha) application rate. For tebuconazole, half life of 6.69 and 7.72days was reported in onion 6 and 0.866 and 1.083 days in case of chilli 5 at the single and double dose, respectively. In other studies, the reported half life was 1.7 days Mohopatra et al 8 and 6days in onion Mohopatra et al 9 and mango 10 5.87 and 6.93 days in watermelon 15 4.49 days in ginseng, 11 1day in chilli 12 and 0.9days in tomato (Sing and Sing, 2014).…”
Section: Dissipation Of Insecticidesmentioning
confidence: 99%